Redo aortic valve reconstruction as saving surgery in a patient with severe rheumatoid cardiac disease - Rojas, Pedro (2021)
The combination of aortic valve regurgitation, rheumatoid aortitis, and subaortic stenosis is not frequent in patients with rheumatoid arthritis. Moreover, the surgical treatment of these entities may be challenging with non-adequate results. We report a case of a patient with severe aortic valve regurgitation, inaccessible aortic root secondary to rheumatoid aortitis, and severe subaortic stenosis initially treated by aortic valve replacement. We reoperated the patient due to acute prosthetic valve failure performing an aortic valve reconstruction using bovine pericardium and Ozaki’s technique with good outcomes.